Submerged-arc welding method of steel for low temperature use
Patent Information
- Application Number
- JP2023143052
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-09-04
AI Technical Summary
【0011】 本発明に係る低温用鋼のサブマージアーク溶接方法によれば、下向、水平すみ肉に加え横向姿勢の溶接において、アークが安定してスラグ剥離性及びビード形状が良好であるなど優れた溶接作業性が得られ、高温割れが生じることなく、溶接金属の低温じん性が良好など高品質な溶接部を得ることができる。
Smart Images

Figure 2025035790000001 
Figure 2025035790000002 
Figure 2025035790000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a submerged arc welding method for low-temperature steel such as 9% Ni steel used in the construction of storage tanks for low-temperature liquids such as LNG, in which the composition of the sintered flux is optimized and the amount of Ni and Al in the welding wire is appropriate, thereby achieving good welding workability in flat and horizontal positions, good toughness of the weld metal, and high-quality welds free from defects such as cracks. [Background technology]
[0002] The submerged arc welding method is widely used for welding low-temperature steels because it is highly efficient and produces high-quality weld metal. In addition to the traditional welding positions such as downward and horizontal fillet, fluxes that enable horizontal welding have been developed and are being applied to on-site construction of tanks.
[0003] Welds of low-temperature steels such as 9% Ni steel are required to have high strength and low-temperature toughness as-welded without post-weld heat treatment, so welding wire with a higher Ni content than the base material is used, and Ni-based alloy wires such as Inconel and Hastelloy, which contain 50 mass% or more Ni, have traditionally been used.
[0004] In on-site construction of tanks, submerged arc welding is applied to welding in the horizontal position in addition to flat and horizontal fillets. In recent years, the development of flux-cored wires for gas-shielded arc welding, which have excellent welding workability in all positions, has been progressing, but blowholes are likely to occur and crack resistance is insufficient, so submerged arc welding and covered arc welding are still the main methods used for important butt joints.
[0005] Conventionally, as for submerged arc welding materials and welding methods for low-temperature steels, for example, Patent Document 1 proposes a flux for submerged arc welding of 9% Ni steel that has excellent welding workability for horizontal fillets and horizontal position welding by optimizing the flux components. However, this submerged arc welding method has problems such as being prone to blowholes and slag inclusion, large irregularities in the bead in the downward position, and an unstable bead shape in the horizontal position, making it difficult to obtain sufficient defect resistance and weld finish for application to on-site welding work in tank construction.
[0006] In addition, Patent Document 2 proposes a submerged arc welding method that can obtain a welded joint with excellent low-temperature toughness and welding workability by optimizing the wire and flux components. However, the technology described in Patent Document 2 contains a large amount of Al2O3, which makes it prone to slag inclusion and reduces defect resistance. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2022-152690 A [Patent Document 2] JP 2018-8293 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been devised in view of the above-mentioned problems, and has an object to provide a submerged arc welding method for low-temperature steel such as 9% Ni steel used in the construction of storage tanks for low-temperature liquids such as LNG, which has a stable arc, good slag removability, good bead shape, excellent cracking resistance, no welding defects, and good weld metal toughness, not only in flat position and horizontal fillet welding but also in lateral position welding. [Means for solving the problem]
[0009] In order to solve the above problems, the present inventors have conducted various studies on the composition of flux for submerged arc welding. As a result, they have found that in order to adjust the bead shape in flat and horizontal welding positions, it is necessary to adjust the BI value, which indicates the ratio of CaO to SiO2 and Al2O3 among the slag additive components, and optimize the balance between slag fluidity and bead formability. They have also found that adding an appropriate amount of metal Al to the welding wire can prevent welding defects such as blowholes and slag entrapment.
[0010] The present invention has been made based on the above findings, and the gist of the present invention is a submerged arc welding method for low-temperature steel, characterized in that the method comprises welding low-temperature steel by combining a sintered flux containing, in mass % relative to the total mass of the sintered flux, 1-20% SiO2, 10-25% Al2O3, 1-20% MgO, 30-60% CaF2, 1-10% CaO, 0.1-5% Na2O, 1-10% CaCO3, and metallic Mn, with metallic Al being 0.1% or less, and the BI calculated from the following formula (1) for the contents of the SiO2, Al2O3, and CaO being 0.32-0.36, with the remainder being impurities, and a welding wire containing, in mass % relative to the total mass of the welding wire, 50-64% Ni and 0.01-0.4 Al. BI=[CaO] / ([SiO2]+[Al2O3])...(1) In formula (1), [CaO], [SiO2], and [Al2O3] represent the mass percentage of each component relative to the total mass of the sintered flux. Effect of the Invention
[0011] According to the submerged arc welding method for low-temperature steel of the present invention, in addition to flat and horizontal fillet welding, excellent welding workability such as a stable arc, good slag removability and good bead shape can be obtained, and high-quality welds can be obtained without the occurrence of hot cracks and with good low-temperature toughness of the weld metal. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The submerged arc welding method for low temperature steel to which the present invention is applied will be described in detail below.
[0013] The submerged arc welding method for low-temperature steel to which the present invention is applied is a method for submerged arc welding low-temperature steel such as 9% Ni steel used as a construction material for low-temperature liquid storage tanks, by combining a sintered flux with a welding wire. The present invention has been made possible by the synergistic effects of the individual and coexisting components of the sintered flux used in submerged arc welding and the welding wire combined therewith. The reasons for adding and limiting each component are described below.
[0014] First, the content of each component of the sintered flux is expressed in mass % relative to the total mass of the sintered flux, and the mass % is simply expressed as %.
[0015] [SiO2: 1-20% by mass relative to the total mass of sintered flux] SiO2 is added from silica sand, wollastonite, etc., with the aim of increasing slag viscosity and improving slag encapsulation. If SiO2 is less than 1%, the effect is not fully obtained and slag encapsulation becomes poor. On the other hand, if SiO2 exceeds 20%, the slag becomes vitrified and breaks into small pieces when removed with a chisel or chipping hammer, making it difficult to remove the fine slag and poor slag peelability. Therefore, SiO2 is set to 1-20%.
[0016] [Al2O3: 10-25% by mass relative to the total mass of the sintered flux] Al2O3 is added from alumina and other materials to raise the solidification point of the slag, shape the bead, and prevent the bead from sagging, especially when in a horizontal position. If Al2O3 is less than 10%, the effect is not fully achieved, and the bead will sag in a horizontal position, making welding difficult. On the other hand, if Al2O3 exceeds 25%, the solidification point of the slag is high, and it will remain at the bottom of the groove, making it more likely that slag will be included. Therefore, the Al2O3 content is set at 10-25%.
[0017] [MgO: 1-20% by mass relative to the total mass of the sintered flux] MgO is added from magnesia clinker to form stable slag even in high current ranges such as submerged arc welding, and to improve slag removability. If MgO is less than 1%, sufficient effect is not obtained and slag removability is poor. On the other hand, if MgO exceeds 20%, pore defects such as pits and wormholes are likely to occur. This is because magnesia clinker raw material is produced by refining magnesium hydroxide formed by the reaction of seawater and lime, and pore defects occur due to crystal water that has not been released. Therefore, MgO is set to 1-20%.
[0018] [CaF2: 30-60% by mass relative to the total mass of the sintered flux] CaF2 is added from fluorite and other materials, and is added to improve arc stability by ionizing in the arc to generate fluorine-based gas. If the CaF2 content is less than 30%, the effect is not fully achieved and the arc state becomes unstable. On the other hand, if the CaF2 content exceeds 60%, spattering occurs and the dispersed flux scatters, making welding work difficult. Therefore, the CaF2 content is set to 30-60%.
[0019] [CaO: 1-10% by mass relative to the total mass of the sintered flux] CaO is added from wollastonite and other materials to increase the basicity of the flux and improve the toughness of the weld metal. If the CaO content is less than 1%, the effect is not fully achieved, and the toughness of the weld metal becomes poor. On the other hand, if the CaO content exceeds 10%, the activating element Ca bonds with the oxygen in the molten pool too early, hindering the maintenance and stability of the arc and making the arc state unstable. Therefore, the CaO content is set to 1-10%.
[0020] [Na2O: 0.1-5% by mass relative to the total mass of the sintered flux] Na2O is added from the solid water glass components such as sodium silicate, and is added for the purpose of lowering the ionization voltage and improving the arc stability. If the Na2O content is less than 0.1%, the effect is not fully obtained and the arc becomes unstable. On the other hand, if the Na2O content exceeds 5%, the flux becomes more susceptible to moisture absorption and is more susceptible to pore defects such as pits. Therefore, the Na2O content is set to 0.1-5%.
[0021] [CaCO3: 1-10% by mass relative to the total mass of the sintered flux] CaCO3 is added from calcium carbonate and other substances, and is decomposed by the heat of the arc to generate CO2 gas, which protects the weld metal by isolating it from the atmosphere, and is added to reduce the amount of oxygen in the weld metal and improve low-temperature toughness. If the CaCO3 content is less than 1%, sufficient effect cannot be obtained, and the amount of oxygen in the weld metal will be high, resulting in low low-temperature toughness. On the other hand, if the CaCO3 content exceeds 10%, the C content in the weld metal will be high, resulting in low low-temperature toughness. Therefore, the CaCO3 content should be 1-10%.
[0022] [Mn metal: 0.1-5% by mass relative to the total mass of the sintered flux] Metallic Mn is added from metallic Mn powder, ferro-Mn powder, etc., and combines with S, an impurity in the weld metal, to become MnS in the weld metal, fixing S, and is added for the purpose of improving hot cracking resistance. If metallic Mn is less than 0.1%, sufficient effect is not obtained, and hot cracking resistance deteriorates. On the other hand, if metallic Mn exceeds 5%, MnS precipitates in excess, causing openings in bending tests of welds and failing the test. Therefore, metallic Mn is set to 0.1-5%.
[0023] [Metallic Al: 0.1% or less by mass based on the total mass of the sintered flux] Metallic Al is added from metallic Al powder, ferro-aluminum powder, etc. Metallic Al added from the flux dissolves when it is directly under the arc and thoroughly mixed with the molten metal, and some of it acts as a deoxidizer, becoming Al2O3 slag that floats to the surface and has the effect of encapsulating the bead surface, but metallic Al from the flux that is dispersed in areas that do not reach a sufficiently high temperature easily bonds with C and N, and when it bonds with C it precipitates as Al4C3, and when it bonds with N it precipitates as AlN, which remains in the weld metal and becomes slag inclusion. Therefore, in order to prevent slag inclusion, metallic Al is set to 0.1% or less.
[0024] The balance of the sintered flux is TiO2, ZrO2, FeO, Fe2O3, K2O, P and S, which are impurities in the raw materials used.
[0025] [BI:0.32~0.36] The BI value, which indicates the ratio of CaO to SiO2 and Al2O3 among the slag additive components, is calculated by the following formula (1). This BI value is an index showing the optimum balance between slag fluidity and bead formability.
[0026] BI=[CaO] / ([SiO2]+[Al2O3])...(1) In the formula (1), [CaO], [SiO2], and [Al2O3] indicate the mass percentage of each component relative to the total mass of the sintered flux.
[0027] If the BI is less than 0.32, the slag fluidity is low, and the bead shape in the downward position is unstable and has many projections and recesses. On the other hand, if the BI exceeds 0.36, the slag fluidity is too high, and the bead shape in the horizontal position is unstable and has many projections and recesses. Therefore, in order to suppress the unevenness of the bead in the downward, horizontal fillet, and horizontal positions and to obtain a smooth and good bead, the BI is set to 0.32 to 0.36.
[0028] Next, the content of each component of the welding wire to be combined with the sintered flux will be described. The content of each component of the welding wire is indicated in mass% relative to the total mass of the welding wire, and the description of the mass% is simply indicated as %.
[0029] [Welding wire Ni content in mass percent of total mass of wire: 50-64%] Next, the welding wire to be combined with the sinterable flux contains Ni at 50% or more by mass% relative to the total mass of the welding wire. If the Ni content of the welding wire is less than 50%, the low-temperature toughness required for a cryogenic liquid storage tank cannot be satisfied. Therefore, the welding wire to be combined with the sinterable flux contains Ni at 50% or more by mass. On the other hand, if Ni is added at more than 64%, the wire becomes expensive and is less economical. Therefore, the Ni content of the wire is set to 50-64%.
[0030] [Welding wire Al content in mass percent relative to the total mass of the wire: 0.01-0.4%] The Al content of the wire acts as a deoxidizer and is added to suppress blowholes in the weld metal. If it is less than 0.01%, the effect of suppressing blowholes is not sufficient. On the other hand, if it is added in excess of 0.4%, it becomes a large oxide, Al2O3, which remains at the bottom of the groove and is prone to slag inclusion. Therefore, the Al content of the wire is set to 0.01 to 0.4%.
[0031] The balance of the welding wire is preferably C: 0.02% or less, Si: 0.1% or less, Mn: 0.8% or less, Cr: 25% or less, Mo: 8-25%, W: 4.5% or less, Fe: 8% or less, and Ti: 0.3% or less. EXAMPLES
[0032] The effects of the present invention will now be described in more detail with reference to examples.
[0033] Table 1 shows various prototype baked fluxes. Table 2 shows the combined welding wires. The wire diameter of the welding wire was 2.4 mm, and the fluxes were dried at 300°C for 2 hours before use, and then exposed to a high-temperature constant-humidity chamber at 30°C and a relative humidity of 80% for 1 hour before being used in the welding test.
[0034] [Table 1]
[0035] [Table 2]
[0036] As a survey item, the toughness evaluation of the deposited metal was performed using a 20 mm thick plate of 9% Ni steel of JIS G 3127:2021 SL9N590Q shown in Table 3 as the base material, and a deposited metal test piece was prepared according to JIS Z 3111:2005. The welding conditions were DC (+) wire polarity and welding in a downward position. The welding current was 360 A, the arc voltage was 30 V, the welding speed was 30 cm / min, and the interpass temperature was 150 ° C or less. The test pieces were V-notch test pieces with a notch from the center of the plate thickness to the center of the deposited metal in accordance with JIS Z 3111:2005, and an impact test was performed. The test temperature was -196 ° C, and the impact test was repeated three times, and an average absorbed energy of 70 J or more was considered good. [Table 3]
[0037] For the bending test, a vertical surface bending test piece according to JIS Z 3122:2013 was taken from the above-mentioned weld metal test piece, and was bent 180° with a bending radius of 33 mm to check for the presence or absence of an opening. If an opening of 3 mm or more was present, it was deemed to be defective.
[0038] The C and O contents of the weld metal were measured by taking chip and pin samples from the center of the weld metal in the downward position and conducting quantitative analysis. Any C content exceeding 0.1% and any O content exceeding 0.06% were deemed defective.
[0039] The welding workability was evaluated by investigating arc stability, spatter generation, slag encapsulation, slag removability, and bead shape during the weld metal test in the above-mentioned downward position. Arc stability was evaluated as unstable when welding was started with a flux spray height of 20 mm over the entire 500 mm weld line, and the arc state became unstable, causing the flux to blow up and expose the arc, requiring flux to be sprayed again. Spatter was evaluated as poor when it did not remain within the sprayed flux but scattered to the outside. Slag encapsulation was evaluated as good when the sprayed flux was removed after welding and the welding slag was uniformly formed on the bead surface, and poor when the slag formed on the toe or top was thin or the bead was exposed and oxidized. Slag removability was evaluated as good when the slag could be removed by light tapping with a chipping hammer, and poor when it could not be removed even with multiple strong taps. Slag removability was also evaluated as poor when the slag was broken into small pieces and could not be removed as a single unit, requiring a long time to remove the slag. The bead shape was determined to be defective when it was significantly uneven and the difference in bead height exceeded 2 mm within a weld length of 500 mm.
[0040] The presence or absence of weld defects was confirmed by visually inspecting the welded parts during the weld metal test in the above-mentioned downward position to confirm the presence or absence of pits, and then conducting a radiography test in accordance with JIS Z 3106. The images of defects in the radiographs were classified to confirm the presence or absence of blowholes, slag inclusions, and hot cracks. If pits, blowholes, slag inclusions, or hot cracks were found, the weld was deemed defective.
[0041] To confirm weldability in the horizontal position, the same base material and groove were used as in the above-mentioned flat position weld metal test, and the welding conditions were wire polarity DC(+), welding current: 360A, arc voltage: 27V, welding speed: 40cm / min, interpass temperature: 150℃ or less, and the bead shape was confirmed to be good or bad. The bead shape was highly uneven, and a bead height difference of more than 2mm over a weld length of 500mm was deemed poor. The results are summarized in Table 4.
[0042] [Table 4]
[0043] Test Nos. 1 to 12 in Table 4 are examples of the present invention, and Test Nos. 13 to 24 are comparative examples. Test Nos. 1 to 12, which are examples of the present invention, have appropriate contents and BI values of SiO2, Al2O3, MgO, CaF2, CaO, Na2O, CaCO3, metal Mn, and metal Al in the sintered flux symbols F1 to F10, and appropriate Ni and Al contents in the combined welding wire symbols W1 to W3, so the arc is stable, the slag encapsulation, slag removability, and bead shape are good, no welding defects occur, the C and O contents of the deposited metal are low, the absorbed energy is high, and the bending performance is good, resulting in extremely satisfactory results.
[0044] In the comparative example, test No. 13, the slag encapsulation was poor because of the low SiO2 content of the sintered flux code F11. Also, the high Al2O3 content caused slag inclusion.
[0045] Test No. 14 had poor slag removability due to the high SiO2 content of the sintered flux code F12. Also, the low Al2O3 content caused the lateral bead to sag, resulting in poor results.
[0046] Test No. 15 had poor slag removability due to the low MgO content of the sintered flux code F13. Also, spatter occurred due to the high CaF2 content.
[0047] In test No. 16, pits occurred due to the high MgO content of the sintered flux F14, and the low CaF2 content caused poor arc stability.
[0048] In test No. 17, the absorbed energy was low because the CaO content of the sintered flux code F15 was low. Also, the BI value was low, so the bead shape in the downward position was poor.
[0049] In test No. 18, the arc stability was poor due to the high CaO content of the sintered flux code F16. Also, the bead shape in the horizontal position was poor due to the high BI value.
[0050] Test No. 19 had poor arc stability due to low Na2O content in the sintered flux code F17. Also, due to high CaCO3 content, the C content was high and the absorbed energy was low.
[0051] In test No. 20, pits were generated due to the high Na2O content of the sintered flux F18. Also, the low CaCO3 content resulted in high O content and low absorbed energy.
[0052] In test No. 21, hot cracking occurred due to the low metallic Mn content of the sintered flux code F19, and slag inclusion occurred due to the high metallic Al content.
[0053] In test No. 22, the bending test was poor because the metal Mn of the sintered flux code F20 was high, and blowholes occurred because the Al of the wire code W4 was low.
[0054] In test No. 23, the absorbed energy was low because the Ni content of the wire W5 was low. Also, slag entrapment occurred because the Al content of the wire W5 was high.
[0055] In test No. 24, the BI value of the sintered flux code F21 was low, so the bead shape in the downward position was poor.
Claims
[Claim 1] In a submerged arc welding method for low-temperature steel, the method comprises the steps of: Yes 2 :1~20%, <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :15~25%、 MgO: 1-20%, CaF 2 :30~60%、 CaO: 1-10%, Na 2 O:0.1~5%、 CaCO 3 :1~10%、 Metal Mn: 0.1 to 5% Metal Al: 0.1% or less, The SiO 2 , Al 2 O 3 The CaO content is such that the BI calculated by the following formula (1) is 0.32 to 0.36, The balance is sintered flux which is an impurity, In mass% relative to the total mass of the welding wire, Ni: 50-64%, Al: 0.01~0.4% 2. A method for submerged arc welding of low temperature steel, comprising the steps of: welding low temperature steel by combining a welding wire containing B.A.R.T. 2 ]+[Al 2 O 3 ])・・・(1) In formula (1), [CaO] and [SiO 2 ], [Al 2 O 3 ] indicates the mass % of each component relative to the total mass of the sintered flux.
Citation Information
Patent Citations
Submerged arc welding method of steel for low temperature use
JP2022152690A
Submerged arc welding method
JP2018008293A